Inter-Female Territorial Behavior In Pampean Grassland Mouse, Akodon Azarae (Cricetidae: Sigmodontinae) - Bonatto, Maria Florencia (2013)
ABSTRACT. In order to study territorial behavior in Akodon azarae females we performed 15 resident-intruder tests between breeding females in 30 individual enclosures. Each enclosure was provided with water and food ad libitum, and shelter. Aggressive behavior infrequent and did not vary between residents and intruders. Resident and intruder spent most of the time exploring the environment, suggesting tolerant coexistence. Our results did not provide evidence of territorial behavior in females, and contradict inter-female spatial avoidance registered in previous studies. We propose future resident-intruder tests including the nest site as defendable resource and a longer previous permanence period in individual enclosures.